The Role of Sradha and Bhakti in Efforts to Increase Happiness in the Era of Information Technology - I Putu Putra Astawa; I Made Endra Lesmana Putra; Ni Putu Suwardhani; Ni Nyoman Sri Winarti (International Journal of Educational Research Excellence (IJERE), 2023)
Religious values in science or providing religious morality to science. Mastery of science and technology is to improve skills in order to improve the quality of human life, while Sradha and Bhakti (faith and piety) are to increase moral values and wisdom. Therefore, touching on religious values that are based on divine teachings is very important. In this way, the goal of Hindu religious education which is in line with the goals of national education can be achieved, namely developing and increasing Sradha (faith) and Bhakti (devotion) of Hindus towards God Almighty/Ida Sanghyang Widhi Wasa through the appreciation and practice of Hindu religious teachings in order to become Hindu people. who is dharmika and able to realize "Moksartham Jagadhita". This research population consists of the UNHI academic community (lecturers, students and education staff). The sampling technique uses probability stratified random sampling with proportional allocation. Data was collected using questionnaires, and then analyzed using quantitative analysis with Structural Equation Modeling (SEM). Based on the results of the analysis, the results of this research show that Sradha and Bhakti have a significant effect on happiness, furthermore, the interaction between Information Technology Modernization and Sradha on Happiness Levels is not significant; The interaction between information technology modernization and devotion to the level of happiness is not significant, and information technology modernization has had a significant influence on human happiness.